PENERAPAN MODEL GAME BASED LEARNING BERBANTUAN MEDIA QUIZIZZ UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR IPAS KELAS V SDN 74/II TANAH PERIUK - Nadia Viarosa; Subhanadri Subhanadri; Nurlev Avana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This Classroom Action Research (CAR) was motivated by the low learning outcomes and learning process of fifth-grade students in Science at SDN 74/II Tanah Periuk. This was evident in the lack of student engagement in learning activities and the average test scores, which were still below the minimum passing grade (KKTP). These scores were still below the Learning Objective Achievement Criteria (KKTP) set by the school, which was 70. The purpose of this study was to describe the application of the Game-Based Learning model, supported by the Quizizz media, to improve the learning process and outcomes of fifth-grade students in Science at SDN 74/II Tanah Periuk. The research method used was Classroom Action Research (CAR). The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 26 fifth-grade students at SDN 74/II Tanah Periuk. Data collection used observation and tests. The data collection instruments used observation sheets and test questions. The observation data were analyzed using descriptive analysis techniques, and the test data were analyzed using formulas. The results obtained from the research include: 1) The implementation of the Game Based Learning model assisted by Quizizz media on the material Chapter 7 My Proud Region is categorized as Very Good. In the assessment of the educator process in cycle 1 it was 80.76% and cycle 2 it was 92.30%. While in the student process in Cycle 1 it was 65.21% and cycle 2 it was 84.77%. So that the results have reached the process success indicator of 75%. 2) Student learning outcomes have increased above the KKTP score of 70, after the implementation of the Game Based Learning model assisted by Quizizz media. The student learning outcomes that were completed in cycle 1 were 69.56%. The student learning outcomes that were completed in cycle 2 were 86.95%. The application of the Game Based Learning model assisted by Quizizz media can improve the process and learning outcomes of students.